Transitioning from interviewer-administered to self-administered survey modes: implications for the quality of political measures - Nursel Alkoç; Michèle Ernst Stähli (Frontiers in Political Science)
Face-to-face surveys have traditionally been regarded as the “gold standard” in data collection. However, due to declining response rates and soaring costs, they have largely been replaced by self-administered methods. This trend has been further accelerated by the COVID pandemic, which has driven even major scientific surveys to adopt self-completion modes. Using evidence from the Swiss European Social Survey (ESS) and the Measurement and Observation of Social Attitudes in Switzerland (MOSAiCH)—the former intending the transition and the latter having already done it, this paper examines the implications of the transition from face-to-face interviews to self-completion questionnaires for the quality of political measures, which are the most frequently used by scholars. We draw our analyses upon telephone, web, and mail questionnaires of the LIVES-FORS mixed mode experiment and to-face interviews of the ESS 2012. The results do not show large mode differences in favor of face-to-face interviews in terms of political measures. On the contrary, telephone, web and paper modes may offer more advantages in certain situations. To better understand the implications of the intended mode transition in ESS, additional analyses were conducted with MOSAiCH, which has the same quality standards as ESS and switched from a face-to-face survey to a self-survey mode already in 2018. The findings suggest that a shift to self-administered questionnaires could provide political estimates that are of similar quality as those from face-to-face interviews.